β-Cyclodextrin modified mesoporous silica nanoparticles as a nano-carrier: Response surface methodology to investigate and optimize loading and release processes for curcumin deliveryβ-Cyclodextrin modified mesoporous silica nanoparticles as a nano-carrier: Response surface methodology to investigate and optimize loading and release processes for curcumin delivery - Abdous, Behnaz; Sajjadi, S. Maryam; Ma'mani, Leila (Journal of Applied Biomedicine, 2017)
β-Cyclodextrin functionalized PEGylated porous silica nanoparticles KIT-6 (denoted as [β-CD@PEGylated KIT-6] NPs) is synthesized and evaluated as an efficient and reliable pH-sensitive nano-carrier. Curcumin (CUR), an anticancer drug, has low solubility and stability and these properties diminished its bioavailability. One way to overcome this problem is employing nano-carrier for delivery of CUR. In this study, the novel [β-CD@PEGylated KIT-6] NPs nano-carrier was employed for CUR delivery successfully. The nano-DDS was characterized using different techniques such as X-ray powder diffraction (XRD), transmission and scanning electron microscopy (TEM and SEM), Fourier transform infrared (FT-IR) spectroscopy, differential scanning calorimeter (DSC), N2 adsorption–desorption measurement, and dynamic light scattering (DLS). In this study, first, the combination of central composite design (CCD) and response surface methodology (RSM) was used to achieve the optimal condition of the loading step with investigation of two important factors: the loading time and the weight ratio of drug to nano-carrier. Maximum loading efficiency 88.55% was obtained at 43 h of loading time and 1.22 of the weight ratio. Then CUR was loaded onto the nano-carrier at this optimal condition and its released was investigated by CCD-RSM. The maximum drug release was obtained at 5.16 of pH and 107 h of release time.
Keywords: Silicon Dioxide; Cell Line, Tumor; Curcumin; Nanoparticles; poréznost; kurkumin; Drug Carriers; Antineoplastic Agents; protinádorové látky; Drug Liberation; nanočástice; Porosity; léky s prodlouženým účinkem; Delayed-Action Preparations; Drug Delivery Systems; oxid křemičitý; nosiče léků; beta-cyklodextriny; lékové transportní systémy; uvolňování léčiv; beta-Cyclodextrins; nádorové buněčné linie